MENGGAGAS IDEOLOGI PERADABAN MODERN MELALUI PENGEMBANGAN TRADISI DAN NILAI-NILAI KEADABAN PESANTREN - Fathor Rachman (State Islamic Institute of Madura, 2015)
Abstract: Pesantren plays its roles by empowering the community and educating the nation through its education and socio-cultural tradition while maintaining its independence and consistency .The community acknowledges pesantren through its education uniqueness has encouraged pesantren to continue as a catalyst and initiative of development in all aspects, especially in responding global developments. The existence of pesantren is established by internalization of